PENGARUH RASA PERCAYA DIRI DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Wahyu Bagja Sulfemi (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2020)
This study aims to look for the effect between self-confidence (X1) and Principal leadership style (X2) and teacher performance (Y). The research methodology uses the descriptive statistical method of the multiple correlation coefficient of the person coefficient of determination and regression analysis. Statistical tests were used t-tests and F tests. Data collection was carried out by distributing questionnaires. The population in this study were all teachers in public and private junior high schools in Ciampea District, Bogor Regency, totaling 172 people while the sample taken was 45 teachers who were randomly selected. Based on the test results there is a positive influence between self-confidence and teacher performance with a correlation coefficient of 0.64, a coefficient of determination 38.8% t count 2.3%> Value of t table 0.02 and a regression equation with Y = 6.00 + 3.23 X1. There is a positive influence between the principal's leadership style and teacher performance with a correlation coefficient of 0.62 and a coefficient of determination of 37.0%. While t arithmetic for 3.184> t table 0.02 with the regression equation Y = 8.3 + 4.3 X2. There is a positive influence between the confidence of the teacher with the correlation coefficient between the two independent variables with related variables equal to 0.645 coefficient of determination 38.8%. F count 14,954> F table 3.23 with the regression equation Y = 126,879 + 0.166 X1 + 160 X2 The better the teacher's trustability and the principal's leadership style are also higher the performance shown by the teacher. Keywords: Self-Confidence, Leadership Style, Teacher Performance, And The Principal